Evaluation of learning outcomes at the Nursing Department in the field of Evidence-Based Medicine with the use of an e-learning Moodle™ platform - Panczyk, Mariusz; Belowska, Jarosława; Zarzeka, Aleksander; Gotlib, Joanna (Nursing Problems / Problemy Pielęgniarstwa, 2015)
Background. Despite the fact that the concept of Evidence-Based Medicine (EBP) is known and accepted by the specialists in the field of health sciences, study curricula realize this principle insufficiently, also when it concerns educating nurses. Aim of the study. Comparative analysis of evaluating students using e-learning tools in the field of “Clinical research and basics of EBM” at the Nursing Department of the Medical University of Warsaw (MUW) between 2013/14 and 2014/15. Material and methods. Two hundred and sixty-two students of post-graduate studies aiming at obtaining the second degree at the Nursing Department at the MUW, including 122 students from the year 2013/14 and 140 students from the year 2014/15. Snapshots representing the result obtained throughout the e-learning course credit, which covered 40 problem questions in total, were used. In order to evaluate learning outcomes achieved by students in two subsequent years, a comparison was carried out of the final credits for both years and reliability of measurement was assessed. Interior compliance of the educational measurement was evaluated using an inter-correlation and multiple regression analysis. Results. The degree of differentiation in scoring and reliability of measurement for both years was very similar (Leven’s test, p > 0.05). However, it was observed that students from the year 2013/14 achieved statistically higher scores than those from the year 2014/15 (U Mann-Whitney test; p = 0.02; d-Cohen = 0.326). Moreover, for both years a similar score obtained in four modules in the field of practical skills was significantly correlated with the overall credit. The above dependencies were also confirmed in the regression analysis. Conclusions. Empirical evidence presented in this paper that would support the efficiency of the didactic process based on e-learning tools allows to assume that the students of Nursing will certainly obtain the necessary competences in the field of EBM.